Constraining the UV with the electroweak effective action - Iberê Kuntz; Amanda Malagi (Journal of High Energy Physics)
Abstract By considering an arbitrary bare action describing BSM physics, we use the Barvinsky-Vilkovisky resummation to obtain the most general non-local electroweak effective action at second order in the field strength. We also include the contribution of the functional measure to the effective action, which is found to modify the Higgs potential by shifting its vacuum value. The resulting effective action provides one-loop corrections to the W and Z boson masses, ultimately leading to the most general expression for the ρ parameter at one-loop. The functional measure plays a pivotal role as it allows the parameterization of ρ in inverse powers of the scale of new physics, while containing non-local form factors. The comparison of ρ with the latest data leads to several constraints on the UV particle spectra of BSM models.